Perbandingan Nilai Kardiorespirasi dan Suhu Tubuh Dugong Dewasa dan Bayi COMPARISON OF CARDIORESPIRATION RATES AND BODY TEMPERATURE IN ADULT AND BABY DUGONG - Suprayogi, Agik; -, Sumitro; Iskandar, Megawati; Sudranto, Rika; Salahudin Darusman, Huda (Jurnal Veteriner; Vol 8 No 4 (2007), 2007)
A study to compare the physiological values (heart beat and respiration rate, body temperature, and electrocardiogram/ECG) between adult dugong (AD) and baby dugong (BD) was carried out. The dugong’s physiological values were examined by patient monitor. The results showed that heart beat rates of baby dugong (87.11+8.70 per minute) was higher than in adult dugong (45.73+4.10 per minute), but no significant difference was observed on the respiration rates between baby dugong (12.89+3.08 per minute) and adult dugong (10.11+3.44 per minute). The body temperature of baby dugong (29.26+0.77oC) was lower than that of adult dugong (31.42 + 0.41) oC. Regular heart beat rhythms was detected on Lead I, II, and III of ECG of both in baby and adult dugong. The ECG values of baby dugong was higher on voltages and shorter in duration (p<0.05) as compared than those of adult dugong. The axis values in adult dugong showed a position more on the right by (+ 90o)–(- 135o) with mean electricity axis (MEA) of +157,5o compared than axis value in baby dugong which appeared to be more on the left by (-32.7o)–(-76.7o) with mean MEA of -54.7o. The differences in cardiorespiration and body temperature values between adult dugong and baby dugong appeared to be due to differences in ages of the mammal, especially related with the differences on the metabolic rate and anatomical growth.
Keywords: Dugong dugon, electrocardiogram, cardiorespiration, body temperature